1992
DOI: 10.1073/pnas.89.15.6953
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of monocyte chemoattractant protein 1 by vascular smooth muscle cells in hypercholesterolemic primates.

Abstract: Atherosclerosis is marked by an overt inflammatory infiltrate, with enhanced recruitment of monocytes/macrophages observed in both human and experimental atherosclerosis. We previously determined that monocyte chemoattractant protein 1 (MCP-1) accounts for virtually all of the chemotactic activity produced by vascular (aortic) smooth muscle cells in culture. We now report that arteries from a primate model of atherosclerosis with dietary-induced hypercholesterolemia exhibit increased levels of MCP-1 mRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
106
2
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(110 citation statements)
references
References 26 publications
1
106
2
1
Order By: Relevance
“…Early studies reported that MCP-1 is present in macrophage-rich atherosclerotic plaques in humans 22 and primates. 23 Oxidized lipids have long been implicated as mediators of atherosclerosis and foam cell formation. 24 Studies by Cushing et al 25 demonstrated that minimally oxidized low-density lipoproteins (LDLs), but not native LDLs, induced MCP-1 production in vascular wall cells such as endothelial cells and smooth muscle cells.…”
Section: Atherosclerosismentioning
confidence: 99%
“…Early studies reported that MCP-1 is present in macrophage-rich atherosclerotic plaques in humans 22 and primates. 23 Oxidized lipids have long been implicated as mediators of atherosclerosis and foam cell formation. 24 Studies by Cushing et al 25 demonstrated that minimally oxidized low-density lipoproteins (LDLs), but not native LDLs, induced MCP-1 production in vascular wall cells such as endothelial cells and smooth muscle cells.…”
Section: Atherosclerosismentioning
confidence: 99%
“…This gene family consists of four subfamilies (CC, CXC, C, and CX3C) whose distinction is based principally on the relative position of the first two highly conserved cysteine residues. Altered expression of chemokines in a variety of diseases, including those of the cardiovascular system, has been established [2][3][4][5][6][7][8][9][10][11][12][13][14]. For instance, the CC chemokine monocyte chemotactic protein-1 (MCP-1) has been implicated in atherosclerosis, having been demonstrated to be present in atherosclerotic plaques [3,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…30 -32 In addition to being secreted by stimulated human macrophages, 33 MCP-1 is also produced by cultured VSMCs and endothelial cells stimulated with cytokines 34 -36 and minimally modified low density lipoprotein. [37][38][39] RANTES and MIP-1␣ expression has also been documented in a range of chronic inflammatory diseases. 5,40 We and others 36,41 have recently demonstrated that RANTES is expressed by stimulated human VSMCs and endothelial cells.…”
mentioning
confidence: 99%